The Mediating Role of Age Productivity on Human Resources Development, Health Infrastructure, and Proverty Level - Pestaria, Anton; Kamaludin, Kamaludin; Husaini, Husaini; Fadli, Fadli (International Review of Management and Marketing, 2022)
Poverty is a classic problem in many regions in Indonesia, including the Bengkulu Province. There are several causes of poverty case in Bengkulu, three of which are low human resources, inadequate rural health infrastructure, and less productive population with productive working age. The purpose of the study is to examine 1) the influence of human resources management, health infrastructure, and productive age partially on poverty in Bengkulu Province, and 2) the influence of human resources, health infrastructure respectively through mediation of productive age on poverty in Bengkulu Province. This study uses a quantitative descriptive approach using secondary data. The research population is all districts/cities in Bengkulu Province totalling 9 districts and 1 city in 2010 – 2019. This study uses saturated sampling. The data was then processed and analyzed using SEM-PLS. The results of the study show that human resources proxied by the Human Development Index (HDI) had a positive effect on the poverty level, health infrastructure had no effect on the poverty level, productive age had no effect on the poverty level, productive age was not a mediating variable between resources and the poverty level, so that cannot be used as a mediating variable, and productive age does not mediate the effect of health infrastructure on poverty levels in Bengkulu Province.